Correlation and path analysis studies in some mutant and non-mutant lines of Indian mustard (Brassica juncea L. Czern. & Coss.) for seed yield and related traits (Journal of Oilseed Brassica, 2025)
Twenty-nine genotypes of Indian mustard comprising of twenty-one M4-5 mutants of the parent varieties TM-2 and PM 27, five newly developed F6-7 lines and three check varieties (TM-2, NRCHB-101 and PM-27) were evaluated in a randomized block design during rabi 2019-20 and rabi 2020-21 to assess the correlation and path coefficients for seed yield and related traits. The genotypes were evaluated for fourteen quantitative characters. Seed yield per plant was positively correlated with number of siliquae on main shoot at the genotypic level. Number of siliquae on main shoot was positively correlated with plant height, main shoot length, siliqua density and 1000-seed weight. Path analysis based on genotypic correlations showed positive direct effects of number of siliquae on main shoot, number of primary branches and secondary branches per plant and seed yield per plant.